2023
DOI: 10.1001/jamanetworkopen.2023.3502
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning–Based Prediction of Attention-Deficit/Hyperactivity Disorder and Sleep Problems With Wearable Data in Children

Abstract: ImportanceEarly detection of attention-deficit/hyperactivity disorder (ADHD) and sleep problems is paramount for children’s mental health. Interview-based diagnostic approaches have drawbacks, necessitating the development of an evaluation method that uses digital phenotypes in daily life.ObjectiveTo evaluate the predictive performance of machine learning (ML) models by setting the data obtained from personal digital devices comprising training features (ie, wearable data) and diagnostic results of ADHD and sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…ML has been effectively applied in the medical field to diagnose neurological disorders, including ASD (Vakadkar et al, 2021 ; Bahathiq et al, 2022 ; Briguglio et al, 2023 ) and ADHD (Slobodin et al, 2020 ; Mikolas et al, 2022 ; Briguglio et al, 2023 ; Kim et al, 2023 ). These studies have demonstrated the potential of ML to increase diagnostic accuracy, reduce time to diagnosis and improve reproducibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ML has been effectively applied in the medical field to diagnose neurological disorders, including ASD (Vakadkar et al, 2021 ; Bahathiq et al, 2022 ; Briguglio et al, 2023 ) and ADHD (Slobodin et al, 2020 ; Mikolas et al, 2022 ; Briguglio et al, 2023 ; Kim et al, 2023 ). These studies have demonstrated the potential of ML to increase diagnostic accuracy, reduce time to diagnosis and improve reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ML classifiers for ADHD have been developed based on clinical and psychological data (i.e. attention, impulsiveness, sleep, and emotional disorders) (Slobodin et al, 2020 ; Mikolas et al, 2022 ; Kim et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adding certain informative features can improve the performance of the model. A previous study, which investigated the use of a machine learning model for predicting the risk of ADHD or pediatric sepsis, has shown the results of adding demographic features or laboratory features compared to using only clinical features [22,23]. In a study about a machine learning model used to predict the risk of pediatric asthma exacerbation, adding environmental features-such as air quality and temperature-improved the performance of the model compared to using only clinical features [24].…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the performance of eight commonly used machine learning classifiers in our PD-STN dataset. It is shown that the LightGBM classifier, a lightweight gradient boosting framework based on decision tree algorithm 23,24 that has been used in multiple sleep-related studies 21,25 , was constantly associated with the highest accuracies as well as a sensible model convergent speed in both the three-class (wake/NREM/REM) and five-class (wake/N1/N2/N3/REM) decoding contexts (Supplementary Fig. 1).…”
Section: Patient Demographics and Determination Of The Best Decodermentioning
confidence: 99%